Self-Shrinkage Behaviors of Waste Paper Fiber Reinforced Cement Paste considering Its Self-Curing Effect at Early-Ages - Zhengwu Jiang; Xiuyan Guo; Wenting Li; Qing Chen (International Journal of Polymer Science)
The aim of this paper was to study how the early-age self-shrinkage behavior of cement paste is affected by the addition of the waste paper fibers under sealed conditions. Although the primary focus was to determine whether the waste paper fibers are suitable to mitigate self-shrinkage as an internal curing agent under different adding ways, evaluating their strength, pore structure, and hydration properties provided further insight into the self-cured behavior of cement paste. Under the wet mixing condition, the waste paper fibers could mitigate the self-shrinkage of cement paste and, at additions of 0.2% by mass of cement, the waste paper fibers were found to show significant self-shrinkage cracking control while providing some internal curing. In addition, the self-curing efficiency results were analyzed based on the strength and the self-shrinkage behaviors of cement paste. Results indicated that, under a low water cement ratio, an optimal dosage and adding ways of the waste paper fibers could enhance the self-curing efficiency of cement paste.